Development of Resistance Butt Welding Technology and Prototype Equipment for Joining Carbide Bar Chain Ripper Teeth of VK-8 Material - Kuchuk-Yatsenko, S.I.; Havrysh, V.S.; Rudenko, P.M.; Nakonechny, A.O.; Shevchuk, S.A.; Zavertanny, M.S. (Science and Innovation, 2024)
Introduction. The need for welding hard alloys with steel occurs in the tool industry and in other engineering industries while manufacturing carbide blanks that cannot be produced by conventional methods of powder metallurgy because of their size or configuration. Problem Statement. The ripper teeth manufacturing from the hard alloys of the tungsten-cobalt group VK8 and steel 40X is an important and urgent task for improving of the bar chain operational reliability. In world practice, the soldering technology is used in an inductor or a gas flame with silver-based solders for manufacturing the teeth. However, this process is characterized by a low productivity and a high cost. Purpose. Development of highly effective and relatively cheap technology to produce the bar chain ripper teeth and equipment for its implementation. Materials and Methods. The research has been carried out on industrial samples of VK-8 hard alloy and 40X steel. The welded joint microstructure has been studied by optical and electron microscopy. Results. The resistance welding technology of carbide bar chain ripper teeth from material VK-8 and steel 40X with the use of an intermediate composite layer has been developed. Experimental equipment based on resistant welding machine and computer control system has been created. Metallographic studies of weld joints have shown that the joints have no defects. The tests of the welded bar chain ripper teeth have proved that they provide the required service life. Conclusions. The developed technology and equipment enable to reduce the cost and to increase the productivity of the welding process in comparison with the existing technologies. It has enabled to replace the imported bar chain ripper teeth with domestic products.